2019
DOI: 10.1021/acsami.9b13891
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Integration of ReS2/Ni3S2 p-n Heterostructure for Enhanced Photoelectrocatalytic Performance

Abstract: The excellent light absorption, low electron–hole recombination rate, and fast reaction kinetics of photogenerated charges are urgently needed for photoelectrochemical (PEC) water splitting. Herein, a novel p-n heterostructure photoelectrode (ReS2/Ni3S2) is constructed via a one-step hydrothermal method, which shows remarkable HER activity under illumination such as a low overpotential (η10) of 106 mV, high IPCE of 10–15%, and good stability. High-resolution transmission electron microscopy (HRTEM) and X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Compared with SnS 2 and In 2 S 3 , a higher photocurrent density of In 4 SnS 8 means that a large number of photogenerated electrons can be generated . At the same time, lower potential means that H + can be enriched on the surface of the catalyst Figure d further shows that the light conditions are beneficial to excite more electrons and drive the reduction of H + on the In 4 SnS 8 surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compared with SnS 2 and In 2 S 3 , a higher photocurrent density of In 4 SnS 8 means that a large number of photogenerated electrons can be generated . At the same time, lower potential means that H + can be enriched on the surface of the catalyst Figure d further shows that the light conditions are beneficial to excite more electrons and drive the reduction of H + on the In 4 SnS 8 surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As we know, the band gaps of Si and ReS 2 are 1.12 eV and 1.51 eV, respectively. 23,31 And it is a typical Z-scheme band structure between Si and ReS 2 . Typically, holes came from the valence band (VB) of Si will recombine with electrons in the conduction band (CB) of ReS 2 to form a recombination center at the interface.…”
Section: Pec Performance and Mechanism Of The Res 2 /N-si Photoanodementioning
confidence: 99%
“…Layered rhenium disulfide (ReS 2 ), as one of the TMDs, has been paid high attention for PEC applications these days due to its suitable bandgap and weak interlayer coupling interactions. [22][23][24][25][26][27] A number of studies have reported the use of ReS 2 /p-Si heterostructures as photocathodes for the HER owing to the enhanced carrier separation and light absorption. [28][29][30] All these studies are based on the p-p junction at the ReS 2 /p-Si interface and near-surface downward band bending of p-type conductivity from ReS 2 nanosheets (NSs).…”
Section: Introductionmentioning
confidence: 99%
“…4 The electrical double layer capacitance is the most commonly used method to determine the electrochemically surface area (ECSA). [31][32][33] Fig. 5a-c shows the CV curves of the three electrodes near open circuit potential by different sweep speeds.…”
Section: Electrocatalytic Propertiesmentioning
confidence: 99%